Moderation of positive muons by helium gas. (November 2019) - Li, Yang; Bao, Yu; Fan, Ruirui; Li, Xiao; Ning, Changjun; Tong, Xin; Wang, Pengcheng
Abstract: Efficiently creating beams of spin-polarized positive muons with energies between eV and keV (so-called slow muon beams) is important for further development and application of muon spin rotation, relaxation, and resonance techniques. One existing moderation method involves the use of wide-band-gap materials as moderators such as rare gas solids and solid nitrogen thin films (band-gap energy between 11 eV and 22eV). Based on this moderation method, we have studied the use of helium gas as a moderator, with the goal of producing the slow muon beam more efficiently. Because of helium's high (24.6 eV) ionization energy and because the cross section for muonium formation is suppressed in helium gas, we expect the production of slow muons using helium gas to be highly efficient.